EL RÉGIMEN IMPOSITIVO SIMPLIFICADO ECUATORIANO COMO RÉGIMEN DE CUMPLIMIENTO TRIBUTARIO - Suárez Masa, Diego Fernando (2016)
The tax reform is being discussed today and deserves special attention by social and economic implications for the country's economic model which we live requires us to be more competitive and in turn accountable to society. To expect different results we must dare to seek new ways of looking at the economy and tax mechanisms as options for an adequate redistribution of wealth. Our Ecuadorian State, with a view to promoting economic development to a certain number of collection systems with the aim to cover fiscal needs and economic dynamism that provides fund that seeks to solve the same levels of infrastructure, training, political stability, security and exercise in the delivery of justice; Tax collection is based on Constitutional and other laws provisions. The Tax Code and the Internal Tax Regime Law of Ecuador, regulations and general circulars are based on the principles of legality, generality, equality, proportionality and non-retroactivity, with the authority to establish, modify or terminate taxes, just for legislation the competent body. The Constituent Assembly of 2008; reformed the Law of Internal Tax Regime of Ecuador; incorporating the Ecuadorian Simplified Taxation System, a system that was created with the purpose of contributing to formalize small businesses, simplifying processes to facilitate compliance with tax obligations by releasing their obligation to keep accounts and filling out forms; all these benefits with the aim of incorporating a tax culture that fosters development in the country, but the facilities are obtained from this regime makes many taxpayers from abusing the rules, applying strategies of evasion and avoidance that can not be quickly identify the controls applied by the Tax Administration. We also have to ensure it does not benefit from becoming a tax shield for organizations or merchants and set minimum holding times for tending reinventions improve national savings through productive investment. I believe that the productive reinvention is an obligation of the companies grow and be competitive in time for the benefit of the State, seek to encourage saving, production and investment, are well managed and shared fairly among its population. To register for the Simplified Taxation System; the entity of the Internal Revenue Service, have to create a table of categories allowing users to, placed by economic activity they are concerned, their gross revenue earned in the last twelve months preceding the date of registration and limits maximum established for each category of activity and income of the taxpayer; this with the intention of making a better permanent development which guarantees equal rights of taxpayers